CONNECTING BADGES: EXPLORING THE UTILITY OF DIGITAL BADGES FOR LEARNING IN AFFINITY SPACES - Duncan, Sean; Huang, Joey (AoIR Selected Papers of Internet Research, 2015)
In recent years, the “digital badge” has become both a cause for excitement within communities that promote digital tools for learning, as well as a cause of concern within critical communities troubled by the potentially overblown rhetoric of these systems’ proponents (see Halavais, 2012, for a recent assessment). While some have advocated for the implementation of digital badges in order to better credentialize, assess, and promote informal learning practices online, there has been very little study of how current, non-educational badging (and other recognition systems) may impact activities within existing online spaces (if at all). In this paper, we present the results of several studies (the Connecting Badges Project), aimed at connecting interaction and digital badges in interest-driven (Ito, et al, 2008) affinity spaces (Gee, 2005; Author, 2012a). The goal of this work is to understand how digital badges may or may not relate to everyday practices “in the wilds” of existing online spaces, and how the activities found within multiple sites might relate to differential uses of badges and recognition systems.